HUBUNGAN KECERDASAN INTRAPERSONAL DENGAN HASIL BELAJAR MATA PELAJARAN PPKN SISWA KELAS V SDIT AL-FITYAH PEKANBARU - Awaliah, Nabilah Putri; Noviana, Eddy; Zufriady (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between intrapersonal intelligence and Civics learning outcomes among fifth-grade students of SDIT Al-Fityah Pekanbaru. This research uses a quantitative approach with a correlational method. The research subjects consisted of 89 students from three different classes. The data collection techniques used were questionnaires to measure intrapersonal intelligence and documentation of report card scores in Civics subject. The results showed no significant relationship between the two variables, with a correlation coefficient of 0.165 and a significance value of 0.127 > 0.05. The contribution of intrapersonal intelligence to Civics learning outcomes was only 2.6%, indicating that other factors influence student achievement in this subject. Thus, intrapersonal intelligence is not a dominant factor affecting learning outcomes in Civics.